Pengaruh Ukuran Perusahaan, Rotasi Audit, dan Komite Audit Terhadap Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2020-2023 - Yahyasari, Sava Dila; Wulandari, Ika (Lembaga Dongan Dosen, 2024)
Research into the impact of a number of factors, including audit rotation, audit committee, and firm size, on mining businesses is the objective of this study. Over the period 2020 to 2023, this study utilized a total of 36 mining companies listed on the Indonesia Stock Exchange (IDX). Information regarding the population was obtained from the official IDX website, which can be found at www.idx.co.id. Over the course of four years, a total of nine companies were monitored, which resulted in a total of thirty-six companies used as research samples collected through a purposive sampling process. For the purpose of this study, quantitative techniques were used, and publicly accessible secondary data was utilized. For the purpose of conducting logistic regression data analysis, SPSS software was used. Based on the results of the study, it can be concluded that firm size does not have a substantial impact on evaluation quality. Meanwhile, audit rotation and audit committee do not have a substantial impact on the quality of audits conducted at the mining companies that are the subject of this study.